Standardization of Therapeutic Measures in Antibiotic Consumption Monitoring to Compare Different Livestock Populations - Hommerich, Katharina; Vogel, Charlotte; Kasabova, Svetlana; Hartmann, Maria; Kreienbrock, Lothar (Frontiers in Veterinary Science, 2020)
Using sales data, information on antimicrobial usage in animals is collected cumulatively across the European Union, which is mandatorily documented and reported by every country and published within annual reports. These serve to perform cross-border comparisons of antimicrobial consumption, despite their ambiguity due to the different units and key figures used. To improve comparability, the European Medicines Agency has introduced the population correction unit (PCU) as a theoretical unit of measurement. This represents the biomass of a livestock population and is related to antibiotic consumption. However, the PCU does not consider the variability of how a livestock population is composed structurally with regard to the proportions of production types contained therein. To achieve better comparability between the different populations, we applied a system of standardization in an artificial example and in real antimicrobial consumption data obtained from the VetCAb-S (Veterinary Consumption of Antibiotics – Sentinel) database. This was done by quantifying the consumption of antibiotics by livestock in exemplary regions by means of the amount of active substance used and subjecting it to a direct standardization procedure to identify and measure differences in consumption in relation to the composition of the population structure. The consideration of the population structure results in substantial effects when comparing antimicrobial usage in livestock. The comparison of antimicrobial usage in two different livestock populations showed that their structural composition has an impact on total consumption. To achieve a more compelling comparability in the context of monitoring antibiotic consumption in livestock populations, we recommend using an indirect standardization method. This assumes that animal populations can be structured accordingly well. Correspondingly, detailed information on antimicrobial usage by species should be available for this type of stratification.